Privação de liberdade e liberdade para falar : ressonâncias da clínica psicanalítica no centro socioeducativo - Débora Ferreira Bossa (2023)
This research entitled “Deprivation of freedom and freedom to speak: resonances of the psychoanalytic clinic in the socio-educational center” came from clinical practice with adolescents undergoing a socio-educational measure of deprivation of liberty in a socio-educational center located in a city in the state of Minas Gerais. The sewing, arrangement between theory, clinic and research that supports psychoanalysis as a field of scientific knowledge, made possible the dialogue between listening to the adolescents and the clinical-political intervention, through which we dedicated /ou all efforts were dedicated to advancing along the singular axes and plural, whose historical-political crossings underlie the know-how in psychoanalysis. Thus, with the guiding question “why crime?”, this thesis was based on the pathway between the clinic, research and writing, with the aim of investigating the logic of insertion and/or permanence of adolescents in crime, based on of psychoanalytic listening to adolescents undergoing socio-educational measures of deprivation of liberty. The following were listed as specific objectives: recognizing the effects of the infraction, identifying the political forms of biopower, necropolitics and the killable lives of neoliberal logic; and, problematize the tension between the deprivation of freedom and analytical listening entangled by the socio-political dimension of Brazilian coloniality and the consequences of racism, articulating the dimensions of colonialism and capitalism. To achieve these objectives, the research was based on the construction of vignettes originated from clinical and institutional scenes, in consultations carried out in the period from 2018 to 2020. Thus, as a methodological foundation it was based on the temporality of Freud's unconscious (1914/2020) - remember , repeat and elaborate - and, as a methodological procedure, it was based on Lacanian logical time (1945/1998) - moment of seeing, time of understanding and moment of concluding - so that development in four stages was possible: analysis of clinical scenes and institutional; literature review; construction of vignettes; composition of clinical and academic writing. The elements were investigated under the life-death and servitude-authorship pairs, whose analyzes identified nodal or paradigmatic points for the analysis of the analyzed phenomenon: the relationship between adolescence and crime.